MODERN EDUCATION AND PEDAGOGY: DEVELOPMENT TRENDS AND PROSPECTS - Ruzieva, Nuriza (MMIT Proceedings, 2023)
In this article, the education system in Uzbekistan, its development trends and prospects are discussed in detail. The role of methods in the educational system is analyzed